Case of high‐risk epithelioid hemangioendothelioma of the neck. Issue 10 (28th September 2012) - Matsuzawa, Shingo; Kanazawa, Takeharu; Yamaguchi, Takehiko; Nishino, Hiroshi; Kawada, Kazumi; Ichimura, Keiichi
<x xml:space="preserve">Abstract</x> Background Epithelioid hemangioendotheliomas (EHEs) of the head and neck region are uncommon malignant neoplasms that exhibit various biologic behaviors characteristic of both low‐ and high‐grade malignancy. A subgroup of EHEs identified as "high‐risk" EHEs because of their size and mitotic activity is associated with an unfavorable clinical course and poor prognosis. Materials and Results We describe the treatment of the first and, in terms of size, largest case of high‐risk EHE arising from the neck. Despite wide excision, recurrence occurred 9 months after surgery, as had been expected. However, the tumor was found to express both vascular endothelial growth factor (VEGF) and VEGF receptor 2, indicating the potential of anti‐VEGF therapy in the treatment of such cases. Conclusion The finding that a high‐risk EHE arising from the head and neck region is characterized by expression of VEGF and its receptor provides further support for the development of targeted molecular therapies. © 2012 Wiley Periodicals, Inc. Head Neck 35: E317–E320, 2013